Groundwater Interacting at Depth With Hot Plastic Magma Triggers Phreatic Eruptions at Yugama Crater Lake of Kusatsu-Shirane Volcano (Japan) - Yaguchi, Muga; Ohba, Takeshi; Terada, Akihiko (Frontiers in Earth Science, 2021)
Interpreting the triggering mechanisms for phreatic eruptions is a key to improving the hazard assessment of crater lakes. Yugama Crater Lake at Kusatsu-Shirane volcano, Japan, is the site of frequent phreatic eruptions with the recent eruptions in 1982–83, 1989, and 1996, as well as volcanic unrest, including earthquake swarms in 2014 and 2018. To understand the magma–hydrothermal interaction beneath Yugama Crater Lake, we analyzed lake waters from November 2005 to May 2021. From 2005 to 2012, Cl and SO4 concentrations decreased slowly, suggesting the development of a self-sealing zone surrounding the crystallizing magma. We focused on Ca, Al, and Si concentrations as representatives of the breach and dissolution of minerals comprising the self-sealing zone and the Mg/Cl ratio as an indicator for enhanced interaction between groundwater and hot plastic rock within the self-sealing zone. In 2006–2007, the Ca, Al, Si concentrations and the Mg/Cl ratio increased. No Cl and SO4 increase during this period suggests the self-sealing zone was leached by deep circulating groundwater rather than by magmatic fluids injection. After the 2014 earthquakes, Ca, Al, and Si increased again but were associated with a significant Cl increase and a pH decrease. We believe that the HCl-rich magmatic fluids breached the self-sealing zone, leading to fluids injection from the crystallizing magma to the Yugama crater. During this period, the Mg/Cl ratio did not increase, meaning that magmatic fluids ascending from the breached area of the self-sealing zone inhibited deep intrusion of fluids into the hot plastic rock region. In 2018, magmatic fluids ascended through the self-sealing zone again with less intensity than in 2014. All eruptions since 1982 have been accompanied by a Mg/Cl ratio increase and a Cl decrease, whereas, when a significant HCl input occurs, as in 2014, no eruptions and no Mg/Cl ratio increase occurred. This demonstrates that the groundwater–hot plastic rock interaction, rather than the magmatic fluids input, played an essential role in triggering phreatic eruptions; i.e., phreatic eruptions can potentially occur without clear signs of fresh magma intrusions.